A dynamic simulation model for building cooling and heating energy considering climate-building system-occupant interactions - Shu Su; Ao Sun; Guozhi Li; Yujie Ding; Ming Xu (Case Studies in Thermal Engineering)
Residential buildings have a significant potential for energy conservation. The building energy consumption process is a complex system influenced by several factors at climate, building system, and occupant levels. This study introduces a novel model based on a multi-agent system to systematically integrate these multiple influencing factors, simulate their interactions, and estimate the resultant cooling and heating energy with dynamic variations over years considered. The automatic dynamic energy simulation was conducted over 30 years considering four temporal parameters (i.e., outdoor temperature, heat transfer coefficient of the building envelope, household type, and behavior pattern of occupants). A case building was used to validate the model, and the dynamic annual results were quite different from the static ones. The dynamic cumulative cooling energy consumption during 31 years was 0.69 % lower than the static one, whereas dynamic cumulative heating energy was 7.53 % higher compared with static energy. It highlighted the importance of considering dynamic multi-agent interactions. Besides, the roles of multiple energy influencing factors and dynamic parameters were compared and discussed. This study provides critical insights into improving building energy performance and offers a rapid and automatic approach for dynamic energy simulation.